Informacioni sistem za upravljanje saobraćajem na JŽ i njegovo mesto u Evropi - ZGONC, Bogdan (Promet - Traffic&Transportation, 2026)
INFORMATION SYSTEM FOR OPERATION AND CONTROL OF TRAFFIC AT YUGOSLAV RAILWAYS AND ITS POSITION IN EUROPE The autor first discusses the aspect and the concept of the information system for traffic management and control at Yugoslav Railways and the present level of introduction of this system at Yugoslav Railways. The author reiterates the current non-uniform aspect of system utilisation at Yugoslav Railways in terms of hardware and software applications while he sees a particular problem in inadequate telecommunications facilities, i.e. relay systems. The accent has been assigned to the fact that in spite of formally reached agreement on construction of a uniform and unique information system for traffic management and control, in practice thoughts are still turned to alternative practical propositions.